Glucose-6-phosphate dehydrogenase deficiency: Enzimatic and molecular analysis in a Bogotá population (2008)
Objective: To determine the frequency of G-6PD and molecular analysis for identification of A+, A- and Mediterranean in healthy persons in Bogotá. Methods: Quantitative spectrophotometric assays for enzyme activity of G-6PD were carried out on the red cells of 348 asymptomatic and healthy adult males and females. Through molecular analysis of DNA from G-6PD deficients the relevant exons were amplified for PCR and then analysed with the restriction enzymes NlaIII, FokI and MboII, for the detection of A+, A- and Mediterranean variants. Results and conclusions: Among 348 samples, 1.4% exhibited total deficiency and 1.7% had intermediate deficiency while 96.3% were normal. The combined prevalence was 3.7%. In enzymatic activity no statistically significance was seen between males and females. No variant was found among these patients and any of the subjects studied displayed any sign of hemolysis and other clinical manifestations. Although it is not yet clearly understood other mechanisms must exist to offer protection from the oxidative stresses. The finding of severe enzyme deficiency in some heterozygote females is due to extreme degree of X inactivation of the normal chromosome. © 2008 Corporación Editora Médica del Valle.